2021
DOI: 10.1007/s12105-021-01294-9
|View full text |Cite
|
Sign up to set email alerts
|

Metastases of Cutaneous Squamous Cell Carcinoma Seem to be the Most Frequent Malignancies in the Parotid Gland: A Hospital-Based Study From a Salivary Gland Center

Abstract: Malignant parotid tumors account for approximately 20% of all parotid lesions. In addition to the various primary parotid lesions there are secondary parotid malignancies, such as metastases or lymphomas. Data on histopathological distribution of all malignancies-including secondary parotid lesions-is limited. Recent evidence indicated a rising surgical incidence of secondary parotid malignancies. This study aims to review the distribution of malignancies in parotid resections from a salivary gland center. A r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Parotid gland SCC is thought to be more often metastatic cutaneous SCC rather than primary disease [ 40 , 61 , 62 ]. Generally it is thought to be a rare type among primary parotid pathology, however, it is considered highly malicious [ 61 , 63 , 64 ], but some epidemiological studies confirm the significant share of SCC among malignancies of parotid gland, especially when only metastases are analysed [ 65 , 66 , 67 , 68 ]. In the study of Mayer et al [ 67 ], SCC accounted for 35.4% of all parotid malignancies, a very similar result to the above analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parotid gland SCC is thought to be more often metastatic cutaneous SCC rather than primary disease [ 40 , 61 , 62 ]. Generally it is thought to be a rare type among primary parotid pathology, however, it is considered highly malicious [ 61 , 63 , 64 ], but some epidemiological studies confirm the significant share of SCC among malignancies of parotid gland, especially when only metastases are analysed [ 65 , 66 , 67 , 68 ]. In the study of Mayer et al [ 67 ], SCC accounted for 35.4% of all parotid malignancies, a very similar result to the above analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Generally it is thought to be a rare type among primary parotid pathology, however, it is considered highly malicious [ 61 , 63 , 64 ], but some epidemiological studies confirm the significant share of SCC among malignancies of parotid gland, especially when only metastases are analysed [ 65 , 66 , 67 , 68 ]. In the study of Mayer et al [ 67 ], SCC accounted for 35.4% of all parotid malignancies, a very similar result to the above analysis. However, it should be emphasised that the vast majority of parotid SCCs are metastases from other sites, and they account for up to 86% of all salivary SCC [ 65 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…9 Cutaneous SCC is globally the most frequent histological type of cancer to metastasize to parotid, followed by melanoma. 10 However, the same is not true in the Indian scenario where these cancers are uncommon owing to high skin pigmentation. The largest Indian study on tumours metastatic to the parotid found eyelid sebaceous carcinoma, another malignant skin appendageal tumour, to be the most frequent metastatic tumour in the parotid.…”
Section: Case Reportmentioning
confidence: 99%
“…Salivary gland (SG) tumors are rare, representing about 3% of all tumors in the head and neck region worldwide 1,2 . Since the beginning of routine application of fine‐needle aspiration cytology (FNAC) in Sweden at the Karolinska institute in 1964, it has gained importance in the diagnostic workup of SG lesions and is here to stay 3 .…”
Section: Introductionmentioning
confidence: 99%